La Repubblica Federale tedesca e la difesa della democrazia (wehrhafte Demokratie) tra l’ascesa dell’estrema destra e crisi dei partiti tradizionali (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
The German Federal Republic and the Defence of Democracy (wehrhafte Demokratie) between the Rise of the Far right and the Crisis of the Traditional PartiesThis paper examines the threats to democracy in the Federal Republic of Germany in light of the rise of the far-right (AfD) and the crisis of traditional parties. Through the lens of wehrhafte Demokratie (militant democracy), it explores the constitutional (Arts. 18, 21, 79.3 GG) and institutional (Federal Constitutional Court, Federal Office for the Protection of the Constitution) mechanisms designed to safeguard the democratic order. The article reflects on the delicate balance between defending democracy and respecting political pluralism, highlighting tensions caused by the political exclusion of AfD in a context of growing fragmentation and polarization. The central challenge, the author argues, is to protect democracy without betraying its founding principles.
Keywords: Democracy; Authoritarianism; Constitution; Far Right; Political representation